The Biological Station ... - Carlin, David (RMIT University, 2024)
Research Background This research is located within the field of literary nonfiction practice, where personal essay intersects travel writing. Theorists of the personal essay, from Adorno to Shields, have argued that the genre can be a way of making accounts of the real that refuse to ignore the locations (embodied, institutional, cultural, and so on) from which the essayist speaks. How can the analytic and expressive techniques of the personal essay be considered alongside new materialist concepts such as atmospheric attunement (Stewart) as a way to respond to the experience of encounter with(in) a foreign place, and how might this suggest new directions for travel writing? Contribution The Biological Station takes an experience of travel-the residency of a white settler Australian at the Kilpisjarvi Biological Station in northern Finland-as material to generate an affective engagement with ideas of home, displacement and the possibilities of 'foreign' encounter, through novel use of the personal essay ...